MUCOCELE IN THE ORAL CAVITY: A CASE SERIES. - RANI, Dr . L JHANSI; VEERESH M; Shanthosh raj.S; ELLAMPALLI, HIMA SAGAR; S.Periyasamy (Student’s Journal of Health Research Africa, 2024)
Mucocele are benign lesions that collect mucus that can develop in the oral cavity at different locations. This case series provides a thorough analysis of mucocele cases diagnosed and treated during a six-month period at ESIC Medical College and Hospital in kk Nagar, Chennai. Five instances in all were found to have lesions in the buccal mucosa of the lower lip. Analysis was done on the clinical and histological characteristics and treatment results. Surgical excision was used to treat the lesions. There were no documented recurrences over the three-month to one-year follow-up period. The clinical presentation, diagnosis, and treatment of mucocele in the oral cavity are highlighted in this case series, with a focus on the significance of early detection and intervention to avoid complications and recurrence.